Nekaj scenarijev vplivov gozdne politike na kroženje ogljika na primeru Slovenije - Golob, Aleksander (Gozdarski vestnik, 2007)
The paper presents a model of carbon flows and pools in forest related organicmatter for the purposes of forest policy. In order to conserve dead organic matter, it is important to prevent litter gathering and forest fires. Under the condition the forest area remains unchanged, special attention should be focused on the living forest biomass, which is being preserved in Slovenian forests through determination of allowable cut. The share of living biomass is estimated to be 53 % and should still be slightly augmented to reach the optimal growing stock. Three scenarios of possible impacts of forestpolicy decisions intended to retard the rising of CO2 concentrations in the atmosphere until the year 2100 have been elaborated. Two scenarios with a balanced level of felling in relation to increment in line with sustainable forest management show better impacts on the carbon cycle than does the scenario according to which forests would be left to natural development with no felling. These effects are due to the role wood products play in the substitution of carbon that would otherwise be released from fossil fuels whenused directly for energy or for the purpose of producing materials which can be substituted by wood products, especially in the building industry. The total retarding effect of the forest-wood sector on CO2 concentrations under the conditions of sustainable forest management and rational use of wood products is estimated at the level of forest wood increment expressed by the CO2 equivalent. This total effect could be sustainable, but the effect of the forests acting as a carbon sink could only last until 2040 under the conditions of multifunctional forest management.
Keywords: gozdarska politika; kroženje snovi; ogljikov krog; konvencije; climate; podnebje; Slovenia; Slovenija